A review of respiratory manifestations and their management in Ehlers-Danlos syndromes and hypermobility spectrum disorders. (21st July 2021) - Chohan, Karan; Mittal, Nimish; McGillis, Laura; Lopez-Hernandez, Laura; Camacho, Encarna; Rachinsky, Maxim; Mina, Daniel Santa; Reid, W Darlene; Ryan, Clodagh Mai; Champagne, Kateri Agnes; Orchanian-Cheff, Ani; Clarke, Hance; et al.
Background: Ehlers-Danlos Syndromes (EDS) and Hypermobility Spectrum Disorders (HSD) are a heterogeneous group of heritable genetic connective tissue disorders with multiple characteristics including joint hypermobility, tissue fragility, and multiple organ dysfunction. Respiratory manifestations have been described in EDS patients, but have not been systematically characterized. A narrative review was undertaken to describe the respiratory presentations and management strategies of individuals with EDS and HSD. Methods: A broad literature search of Medline, Embase, Cochrane Database of Systematic Reviews, and Cochrane CENTRAL was undertaken from inception to November 2020 of all study types, evaluating EDS/ HSD and pulmonary conditions. This narrative review was limited to adult patients and publications in English. Results: Respiratory manifestations have generally been described in hypermobile EDS (hEDS), classical and vascular EDS subtypes. Depending on EDS subtype, they may include but are not limited to dyspnea, dysphonia, asthma, sleep apnea, and reduced respiratory muscle function, with hemothorax and pneumothorax often observed with vascular EDS. Respiratory manifestations in HSD have been less frequently characterized in the literature, but exertional dyspnea is the more common symptom described. Respiratory symptoms in EDS can have an adverse impact on quality of life. The respiratory management of EDS patients has followed standard approaches with thoracotomy tubes and pleurodesis for pleural manifestations, vocal cord strengthening exercises, continuous positive pressure support for sleep apnea, and exercise training. Reduced respiratory muscle function in hEDS patients responds to inspiratory muscle training. Conclusion: Respiratory symptoms and manifestations are described in EDS and HSD, and have generally been managed using conservative non-surgical strategies. Research into the prevalence, incidence and specific respiratory management strategies in EDS and HSD is needed to mitigate some of the associated morbidity.